(untitled) (Czech Journal of International Relations, 1997)
The Stockholm International Peace Research Institute (SIPRI) is a white crow among other institutes dealing with international relations and politics. It was created in order to deny one of the taboos of world politics - it started to publish until then strictly classified data on the production of weapons in individual countries and on the world trade in them. Today, it has expanded its program to include the publication of data on the movement of nuclear fissionable materials in the world. Last year, the aforementioned institute celebrated its thirty years of existence. Thirty is not an age, but like any anniversary it is a good opportunity to look back and to the future. We also used it to interview the current director of SIPRI, dr. by Adam Daniel Rotfeld about the new challenges facing the world today. We "started" the interview with a rather undiplomatic personal question.